An Analysis of Mudhrabah Contract, Profit Sharing Rate, and Grant (Hibah) of Mudharabah Influence Customer’s Interest to do Saving Case Study: Muamalat Bank, Sragen Branch in 2017 - Kamaluddin, Imam; Cahyo, Eko Nur; Triani, Finis (University of Darusssalam Gontor, 2018)
The purpose of this research is to analyze the influence of mudharaba contract, profitsharing rate and grant of mudharabah muthlaqah contract on customer’s interest to do savingand to ascertain how the mechanism of grant distribution on the mudharabah muthlaqahcontract in Muamalat Bank of Indonesia, branch of Sragen. The findings are that MudharabaContract, Profit Sharing Rate and Grant on the Mudharabah contract, had influenced thecustomer’s interest to do saving in Muamalat Bank. Resulted that F test had shown F point asmuch as 2,783 with significant point as much as 0,165 more than 0.05, while determinationcoefficient was shown by R2 as much as 0.093 or 9,3% had influenced on the customer’sinterest to do saving, while the 90,7% had influenced by other factor.